"String Hallucinations": Multimodal Tactile and Visual Hallucinations in Parkinson's Disease. Issue 2 (23rd November 2015) - Pérez‐Pérez, Jesús; Pagonabarraga, Javier; Fernández‐Bobadilla, Ramón; Kulisevsky, Jaime
Abstract: The aim of this work was to report on 7 patients presenting a distinctive form of multimodal (tactile and visual) hallucinations for which the term "string hallucinations" is proposed. Having observed a patient interacting with imaginary strips of skin in his hands at our movement disorders unit, we prospectively studied PD patients and caregivers over a 6‐month period using a semistructured interview addressed to this particular phenomenon. Demographic characteristics as well as cognitive and motor function were assessed. A total of 7 of 164 PD patients (4.3%) observed during the study period had string hallucinations. One patient was cognitively intact and the other 6 had some degree of cognitive impairment. Common to the phenomenology of the hallucinations was the unpleasant feeling and vision of threads emerging from the subjects' hands. Patients interacted with these "threads, " trying to remove them from their hands. Our study identifies a previously undescribed type of hallucinations in PD, characterized by a complex pattern of multimodal tactile and visual hallucinations.